PENINGKATAN KEMAMPUAN MENULIS ARTIKEL ILMIAH POPULER SISWA KELAS IX SMP NEGERI I BRINGIN DENGAN PEMBELAJARAN SAINTIFIK BERBASIS MEDIA MASSA - Sukardi Ks; Bambang WR; Indah Sugiyarti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2016)
The research aimed at knowing to what extent (1) the effectiveness of Mass Media Based Scientific Approachas to improve the ability to write popular scientific articles, (2) the improvement ofNinth Junior High students? activity, enthusiasm, concentration and creativityin the learning process, and (3) the improvement of Ninth Junior High students? achievement in writing popular scientific article at Negeri 1 Bringin Semarang District after the implementation of mass media based scientific approach. It was a classroom action research (PTK), consisting of components of planning, implementation, observation, and reflection. It included two cycles. The first cycle was implenting scientific approach by utilizing the video "Fighting Student" printed media based. The second cycle was by utilizing the video song entitled "Mirassantika" internet-media based. The subjects of the research were ninth-grade students of SMPN 1 Beringin Semarang in the academic year of 2015/2016. The data of the study consisted of primary data, which were the ninth-grade students, and the secondary data, consisting of the teachers in the classroom, the researcher, fellow teacher of Indonesian, and staf members of UPBJJ-UT Semarang. The results showed that (1) learning to write a scientific article by implenting mass media-based scientific approach could enhance the activity, vigor, enthusiasm, and creativity into learning, (2) enabling to create a condusive atmosphere of effective, interesting, and fun learning, in which up to the end of second cycle 43.75% of students were having happy expression when they were learning and 56.25% of students stated enjoying to follow the lesson: Bahasa Indonesia. Then, 9.38% of the students expressed their creativity greatly increased, 87.56,% of students stated their creativity increased as well. Moreover, 37.5% of students stated that their creativity were improved, also 62.5% of students stated the same idea. Additionally, 46.88% of students stated that they were very attracted to learn bahasa Indonesia and 17.53% of students gained high interest of learning bahasa Indonesia, and (3) improve the number of students who were able to write popular scientific articles with minimal score 78. By the end of second cycle of the number of students who gained score 78 or more were 31 students or if it was calculated in percentage was 96.87%. Thus, it is concluded that the indicators of research have been reached.